Positive aspects of the cycling tourism development on the tourist destination: Case study Fruška gora mountain - Vujko Aleksandra (University Educons, Faculty of Sports and Tourism, Novi Sad, 2012)
Positive aspects of the cycling tourism development on the tourist destination would be in a series of direct and indirect economic effects. These effects would be the first noted among the local population. Cycling tourism development has reflect an order to the opening of new jobs and encouraging the private entrepreneurship. Bearing in mind that the Cycling tourism are sustainable form of tourism the results of research gave guidelines for future development of cycling tourism on Fruška gora mountain. Most important goals were to show the views of Cyclists on Fruška gora Tourist Destination and that the positive aspects of the development of cycling tourism on Fruška gora mountain use as well as a starting point of cycling tourism development on any tourist destination. Empirical research conducted on a sample of 264 cyclo tourists was aimed to present the main benefits of cycling tourism in the area of Fruska gora mountain. Using the Survay method, data indicate that this situation is directly linked with the human resources in the broadest sense.